Blockchain and Data Security Management in Financial Services: A Strategic Evaluation with the COBIT 2019 Framework - Desinta Riski Ashari; Khusnul Khotimah; Samuel Domatius Surya Putra; Adz Dzukran Zaki Zharauri Naimullah Shalih; Angga Rafael Cristian Tambun; Meisyanda Adelia Rahma Putri; Jessica Joylynn Kaligis (Universitas Negeri Surabaya, 2026)
In the digital era, data security is a top priority for the banking industry, given the increasing cyber threats and the demands of strict regulatory compliance. This study aims to analyze the impact of blockchain on data security, regulation, and business efficiency in the banking sector, and provide strategic recommendations for companies that want to adopt this technology. The method used is the Systematic Literature Review (SLR) with the PRISMA approach and bibliometric analysis using Publish or Perish and VOSviewer to identify research trends from 2015 to 2025. The case study at Bank XYZ emphasizes the importance of using the COBIT 2019 framework in evaluating and improving IT infrastructure, as well as the need for better risk management and increased collaboration between teams to achieve higher effectiveness. The results of the study show that blockchain technology, IT governance, and cybersecurity are the main pillars in the digital transformation of banking, where the integration of the three can improve efficiency, security, and transparency in digital financial services, although challenges such as cyber threats, regulation, and risk management still need to be overcome to achieve sustainable optimization. However, challenges such as implementation complexity, high costs, and dynamic regulatory changes are still major obstacles. Therefore, this study recommends the implementation of risk-based security strategies, increasing cyber awareness in the workplace, and utilizing cutting-edge technologies such as artificial intelligence (AI) in data protection systems. With a more adaptive approach, banks can strengthen their security systems and minimize potential cyber threats.